Optimization Strategy for Winning Construction Management Consultant Services Tenders in Indonesia: Delphi and SWOT Studies - Gantika, Eko; Wahyudi, Slamet Imam; Wibowo, Kartono (ASTONJADRO, 2025)
This study aims to formulate an optimization strategy for winning tenders for construction management consulting services in Indonesia based on the results of Delphi and SWOT analyses. The Delphi method is used to obtain consensus from experts on factors that influence tender winning, while the SWOT analysis helps group these factors into categories of strengths, weaknesses, opportunities, and threats. The results show that the company’s main strengths are project experience, quality of human resources, and financial stability. The main weaknesses include inefficient administrative management and incomplete documents. The greatest opportunities arise from national infrastructure projects and partnerships with foreign companies, while the greatest threats are increasingly fierce competition and complex changes in tender regulations. Based on these results, the recommended optimization strategy involves improving project management, utilizing technology, and strengthening relationships with project owners. This study provides strategic guidance that can help consulting firms improve their competitiveness in the tender process.